(untitled) (Journal of Social Sciences Review, 2023)
The events on September 11, 2001, changed the geopolitics of the world and caused diplomatic ties to be rebalanced everywhere. The strategic, political, and military ramifications of Pakistan’s and the United States’ diplomatic reunion after 9/11 are examined in this paper. We look at the background that caused the two countries to become apart and the sharp change in their relationship after the attacks. The article explains how Pakistan’s participation in the U.S. campaign against terrorism ushered in a new phase of bilateral interaction. It explores the difficulties and complexity of this alliance, including problems with sovereignty, security, and regional stability. The paper will also examine the long-term effects of this diplomatic reunion on the geopolitical environment of South Asia generally and Pakistan-U.S. relations specifically. By means of this analysis, the paper highlights the continuous significance of Pakistan-U.S. ties in the framework of global security and provides insights into the changing dynamics of international diplomacy in the post-9/11 period.